Knowledge, Attitude and Practice of Disaster Preparedness Among Health Care Workers in a tertiary care center of Central Nepal - Thapa, Rashmi; Yadav, Mandeep Kumar; Pokharel, Mohir; Chhetri, Dinesh; Neupane, Durga; Mandal, Sobha; Shahi, Makendra Bahadur (Journal of Karnali Academy of Health Sciences, 2022)
Background: An increase in the number of natural disasters and consequently the rate of disabilityhas been also increased. So, purpose of this study is to assess the knowledge, attitude and practiceabout disaster preparedness among health care workers at a tertiary care center of a disaster-pronedeveloping country like Nepal.Methods: This is a descriptive cross-sectional study. A total of 135 participants were included. Self-administered multiple sets of questionnaires with four sections i.e., Demographic information,Knowledge Questionnaire, Aptitude Checklist, and Practice based questionnaire were used for study.The study was conducted in Kathmandu Medical College Teaching Hospital and the study periodwas two months, from December 2021 to February 2022. The respondents were the staffsworking in Kathmandu medical college teaching hospital with or without formal training andwork-related experiences of disaster preparedness and management in the past. The data wasentered into the Microsoft Excel software and analyzed using the statistical package for socialstudies (SPSS) software 23.0 version and P-value was set at 0.5 with 95% CI.Results: Among 135 participants, female participants were 90 (66.7 %). There were 41 Doctors(37.0%) and 45 nurses (37.8%). Equal participation from every department was ensured. Theiroverall knowledge, attitude, and practice in disaster preparedness were good. 80.7% of theparticipants had knowledge of the disaster, and 7.0% agreed with the necessity to have a disasterplan.Conclusions: Health Care professionals have a significant level of knowledge. Attitude is asignificant predictor of readiness to practice. Educators and health policymakers should build arobust curriculum in disaster medicine management and preparedness for the future of competenthealth care professionals in our country Nepal